Early Visual Processing of Feature Saliency Tasks: A Review of Psychophysical Experiments - Kamkar, Shiva; Moghaddam, Hamid Abrishami; Lashgari, Reza (Frontiers in Systems Neuroscience, 2018)
Visual attention has an undeniable impact on our perception. Human brain is unable to process all of the information it faces with in a scene so, the most salient part of it will be chosen to process. This happens involuntary immediately after looking at a scene. It is commonly believed that neural activity in early visual areas induce a part of the scene salient than the others. Various researches since many years ago have shown that our neurons in early visual processing areas, from retina to LGN and then primary visual cortex are selective to some specific features. Everything we see and understand from the visual scene is based on these features and then the combination of them in higher visual areas. Different experiments are designed till now to investigate the impact of these features on saliency and understanding the mechanism behind this using different methods. The focus of this paper is on psychophysical tasks that are designed by researchers to study the role of early visual features in understanding saliency. Although most of them follow the same pattern to create saliency in their designed task, creativity and novelty is used in some tasks which leaded to interesting results. Various tasks designed to answer different questions related to low-level feature contrast are reviewed in this paper. Important and open questions also are discussed. One might extend this to investigate the impact of higher-level features in saliency in complex scenes or natural images.